Multivariate Stochastic Simulation of Wind-solar-hydro Resources Considering Spatio-temporal Correlations - CHENG Qiuyu; HUANG Qiang; MING Bo; CHEN Jing; LI Yan (Renmin Zhujiang)
Complementary operation of wind-solar-hydro resources is an effective mean to promote the consumption of new energy and improve resource use efficiency.Synchronous simulation of wind-solar-hydro resources can provide reliable data for the planning,design,management and risk assessment of the complementary system.Taking ten million-kilowatt-class wind-solar-hydro complementary system upstream Yellow River as an example,after proposing a multivariate stochastic simulation method with consideration of spatio-temporal correlations between wind-solar-hydro resources,this paper firstly analyzes the spatio-temporal correlations of wind-solar-hydro resources,with runoff as the main variable,and wind power and photovoltaic power output as the slave variable for the stochastic simulation;secondly,simulates the runoff in different time series by a seasonal autoregressive model;finally,simulates the photovoltaic power output by the Copula function and conditional probability formula according to the correlation analysis between runoff and wind and photovoltaic power output,as well as the wind power output by a seasonal autoregressive model.The results show that the proposed method can accurately simulate the multivariable time series that can satisfy the historical statistical regularity.